PERBANDINGAN KUALITAS HIDUP PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS DENGAN MENGGUNAKAN KUESIONER COPD ASSESSMENT TEST (CAT) DAN CLINICAL COPD QUESTIONNAIRE (CCQ) - CUT NYAK NAHDAH; SRI REZEKI ARBANINGSIH (JURNAL ILMIAH MAKSITEK, 2021)
Chronic Obstructive Pulmonary Disease is a progressive and life-threatening disease that is estimated to affect more than251 million people worldwide. 2 Whereas according to Riskesdas 2013 is 3.7% or around 9.2 million people. 3 Currently thefourth leading cause of death in the world, causes more than 3 million deaths every year. COPD is estimated to be the thirdleading cause of death in the world in 2020.2 According to a 2017 study it was found that the estimated prevalence ofchronic obstructive pulmonary disease is 1% in the ordinary population and increased in people aged 40 years. 4 In COPD,the effectiveness of treatment is not only obtained from clinical parameters course, but also more to the parameters of thepatient's perspective, namely quality of life. CAT is a validated and standardized questionnaire used to assess the healthstatus of COPD patients. In addition, CCQ is also made to measure the clinical health status in patients, including airwaysymptoms, physical activity limitations, and emotional dysfunction.To determine the difference in quality of life between thequestionnaire according to the CAT and the quality of life according to the CCQ questionnaire and to know thecharacteristics of the respondents namely gender, age, duration of smoking history, pulmonary function / FEV1, in patientswith chronic obstructive pulmonary disease. Descriptive analytic using cross sectional design. The data obtained are primarydata with 53 samples and then analyzed using the Spearman. Spearman test results show that there is no significantdifference between the quality of life of COPD patients using the COPD Assessment Test (CAT) questionnaire and ClinicalCOPD Questionnaire (CCQ), which is p = 0,000 (p <0.05) with a correlation coefficient of 0.815. There was no significantdifference between the quality of life of COPD patients using the COPD Assessment Test (CAT) questionnaire and theClinical COPD Questionnaire (CCQ).